discriminative appraoch based on deep learning model for covid-19 detection from (chest x -ray or ct -scan) images and cough audios - hassani, abde nour; hkammes, abdallah (universty of elouedجامعة الوادي, 2021)
"أدى COVID-19 ، المعروف أيضًا باسم الفيروس كورونا ، إلى شلل جزئي للعالم من جميع النواحي تقريبا، أكثر من 177 مليون شخص في جميع أنحاء العالم مصابين به، وتسبب في وفاة أكثر من 4 مليون شخص، تشمل الأعراض المبكرة للفيروس صعوبة في التنفس والحمى والإرهاق وأكثر من 60 ٪ من الناس يعانون من السعال الجاف. في العقود الماضية ، أظهر مجال الرؤية الحاسوبية والتعلم العميق والآلي .... تحسنًا كبيرًا ويتم تطبيقه الآن في العديد من المجالات مثل الأمن والطب والسيارات ذاتية القيادة ... الانتشار السريع لهذا الوباء دفعنا إلى إثارة عقولنا وإيجاد الحلول واستغلال التكنولوجيا المتاحة للاستفادة منها للحد من تأثير الوباء. لهذا اقترحنا طريقتين، الاولى هي عبارة عن مصنّفًا للسعال يعتمد على التعلم الآلي ل COVID-19 قادر على التمييز بين السعال الإيجابي ل COVID-19 من سعال COVID-19 السلبي والصحي المسجل على الهاتف الذكي، وهذا يساعد في التباعد الاجتماعي وتقليل من كثرة الذهاب الى المستشفيات، اما الطريقة الثانية فهي مكملة للاولة وهي عبارة عن شبكة عصبية تلافيفية عميقة من أجل اكتشاف COVID-19 باستخدام الأشعة السينية للصدر الصور x-ray ، وهذا لمساعدة الاطباء في اتخاذ القرارة الصحيحة في التشخيض . بعد عدة اختبارات وطرق مختلفة لاستخدام موديلات CNN (VGG16 ، Resnet50 ( ... يمكننا القول إننا وصلنا إلى النتيجة المرجوة والتي بلغت 83.4 ٪ للطريقة الأولى و 96.88 ٪ للطريقة الثانية.""COVID-19, also known as the Corona virus, has partially paralyzed the world in almost all respects, more than 177 million people worldwide are infected with it, and it has caused the deaths of more than 4 million people, early symptoms of the virus include difficulty breathing, fever and fatigue More than 60% of people suffer from a dry cough. In the past decades, the field of computer vision, deep learning and automated....has shown great improvement and is now being applied in many fields such as security, medicine, self-driving cars... the rapid spread of this pandemic prompted us to stir our minds, find solutions and exploit the available technology to benefit from it to reduce the impact of the pandemic. That's why we proposed two methods, the first is a machine learning-based COVID-19 cough classifier that is able to distinguish between a positive COVID-19 cough from a healthy and negative COVID-19 cough recorded on a smartphone, and this helps with social distancing and reduce the number of going to the hospital, and the second method is complementary to the first, which is a deep convolutional neural network in order to detect COVID-19 using chest x-ray images, and this is to help doctors make the right decisions in the diagnosis. After several tests and different methods of using CNN models (VGG16, Resnet50)..., we can say that we have reached the desired result, which amounted to 83.4% for the first method and 96.88% for the second method."
mémoire master informatique
Keywords: كورونا - السعال - الصورة السينية; corona - cough - X-rays